Impaired muscle spindle function in murine models of muscular dystrophy. (21st February 2020) - Gerwin, Laura; Rossmanith, Sarah; Haupt, Corinna; Schultheiß, Jürgen; Brinkmeier, Heinrich; Bittner, Reginald E.; Kröger, Stephan
Abstract : Key points: Muscular dystrophy patients suffer from progressive degeneration of skeletal muscle fibres, sudden spontaneous falls, balance problems, as well as gait and posture abnormalities. Dystrophin‐ and dysferlin‐deficient mice, models for different types of muscular dystrophy with different aetiology and molecular basis, were characterized to investigate if muscle spindle structure and function are impaired. The number and morphology of muscle spindles were unaltered in both dystrophic mouse lines but muscle spindle resting discharge and their responses to stretch were altered. In dystrophin‐deficient muscle spindles, the expression of the paralogue utrophin was substantially upregulated, potentially compensating for the dystrophin deficiency. The results suggest that muscle spindles might contribute to the motor problems observed in patients with muscular dystrophy. Abstract: Muscular dystrophies comprise a heterogeneous group of hereditary diseases characterized by progressive degeneration of extrafusal muscle fibres as well as unstable gait and frequent falls. To investigate if muscle spindle function is impaired, we analysed their number, morphology and function in wildtype mice and in murine model systems for two distinct types of muscular dystrophy with very different disease aetiology, i.e. dystrophin‐ and dysferlin‐deficient mice. The total number and the overall structure of muscle spindles in soleus muscles of both dystrophic mouse mutants appeared unchanged. Immunohistochemical analyses of wildtype muscle spindles revealed a concentration of dystrophin and β‐dystroglycan in intrafusal fibres outside the region of contact with the sensory neuron. While utrophin was absent from the central part of intrafusal fibres of wildtype mice, it was substantially upregulated in dystrophin‐deficient mice. Single‐unit extracellular recordings of sensory afferents from muscle spindles of the extensor digitorum longus muscle revealed that muscle spindles from both dystrophic mouse strains have an increased resting discharge and a higher action potential firing rate during sinusoidal vibrations, particularly at low frequencies. The response to ramp‐and‐hold stretches appeared unaltered compared to the respective wildtype mice. We observed no exacerbated functional changes in dystrophin and dysferlin double mutant mice compared to the single mutant animals. These results show alterations in muscle spindle afferent responses in both dystrophic mouse lines, which might cause an increased muscle tone, and might contribute to the unstable gait and frequent falls observed in patients with muscular dystrophy. Key points: Muscular dystrophy patients suffer from progressive degeneration of skeletal muscle fibres, sudden spontaneous falls, balance problems, as well as gait and posture abnormalities. Dystrophin‐ and dysferlin‐deficient mice, models for different types of muscular dystrophy with different aetiology and molecular basis, were characterized to investigate if muscle spindle structure and function are impaired. The number and morphology of muscle spindles were unaltered in both dystrophic mouse lines but muscle spindle resting discharge and their responses to stretch were altered. In dystrophin‐deficient muscle spindles, the expression of the paralogue utrophin was substantially upregulated, potentially compensating for the dystrophin deficiency. The results suggest that muscle spindles might contribute to the motor problems observed in patients with muscular dystrophy.